DNA Barcoding Mushroom Spawn Using EF-1α Barcodes: A Case Study in Oyster Mushrooms (Pleurotus) - Zhao, Peng; Ji, Sen-Peng; Cheng, Xian-Hao; Bau, Tolgor; Dong, Hong-Xin; Gao, Xing-Xi (Frontiers in Microbiology, 2021)
Oyster mushrooms (genus Pleurotus) are widespread and comprise the most commonly cultivated edible mushrooms in the world. Species identification of oyster mushroom spawn based on cultural, morphological and cultivated characteristics is time-consuming and can be extraordinarily difficult, which has impeded mushroom breeding and caused economic loss for mushroom growers. To explore a precise and concise approach for species identification, the nuclear ribosomal internal transcribed spacer (ITS), 28S rDNA, and the widely used protein-coding marker translation elongation factor 1α (EF-1α) gene were evaluated as candidate DNA barcode markers to investigate their feasibility in identifying 13 oyster mushroom species. A total of 160 sequences of the candidate loci were analyzed. Intra- and inter-specific divergences and the ease of nucleotide sequence acquisition were the criteria used to evaluate the candidate genes. EF-1α showed the best intra- and inter-specific variation among the candidate markers and discriminated 84.6% of the species tested, only being unable to distinguish two closely related species P. citrinopileatus and P. cornucopiae. Furthermore, EF-1α was more likely to be acquired than ITS or 28S rDNA, with an 84% success rate of PCR amplification and sequencing. For ITS and 28S rDNA, the intraspecific differences of several species were distinctly larger than the interspecific differences, and the species identification efficiency of the two candidate markers was worse (61.5% and 46.2%, respectively). In addition, these markers had some sequencing problems, with 55% and 76% success rates of sequencing, respectively. Hence, we propose EF-1α as a possible DNA barcode marker for oyster mushroom spawn.